Determinant Factors of Stress Family Caregiver in Caring for Stroke Patients: A Literature Review - Bela, I Kade Miki Indra; Kamaryati, Ni Putu; Darmini, A.A. Ayu Yuliati; Sanjana, I Wayan Edi (Babali Publisher, 2025)
Introduction: Stroke is a common disease that disrupts daily activities and can even lead to death. According to the World Health Organization (2016), stroke is the leading cause of disability worldwide and the second leading cause of death. Stroke affects various aspects of life, including mobility, emotions, attitudes, and communication. Stroke patients often experience activity limitations, making them dependent on family caregivers for assistance with daily needs. This dependency can place a significant burden on family caregivers, leading to stress. This research aims to analyze the key factors contributing to stress among family caregivers of stroke patients. Methods: This study employed a literature review approach, analyzing 16 articles published between 2017 and 2024 in either Indonesian or English. Only full-text articles were included. The literature review followed the PRISMA checklist to ensure the appropriate selection of studies aligned with the research objectives. Results: Several factors contribute to stress among family caregivers of stroke patients, including (1) age, (2) duration of caregivers, (3) gender, (4) burden, and (5) (1) age, (2) duration of caregiving, (3) gender, (4) burden, and (5) social support received from other family members. Conclusion: This highlights the need for tailored stress management strategies, stronger social support networks, and further research to understand varying stressors. Policymakers and healthcare providers should prioritize creating resources, raising awareness, and offering personalized support to alleviate caregiver burden and improve overall well-being.